Composition of tanshinone, ligustrazine and ferulic acid embedded hyaluronic acid hydrogel as well as preparation method and application of composition
By embedding a composition of tanshinone, ligustrazine and ferulic acid into hyaluronic acid hydrogel, core-shell structured drug microspheres and a three-dimensional gel network were constructed, which solved the problem of postoperative adhesion of the intrauterine cavity, achieved stable chimerism and sustained release of the drug, promoted tissue repair and reduced inflammatory response.
Patent Information
- Application Number
- CN202511110174.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-09-19
AI Technical Summary
Existing technologies have problems in preventing postoperative re-adhesion of the intrauterine cavity, such as short maintenance time, poor biocompatibility, or inability to exert multiple pharmacological effects simultaneously. Especially in female patients who need to retain their reproductive function, postoperative re-adhesion of the intrauterine cavity may lead to serious consequences.
A composition of tanshinone, ligustrazine and ferulic acid embedded in hyaluronic acid hydrogel is used. By constructing drug microspheres with a core-shell structure and building a three-dimensional gel network with sodium hyaluronate, gelatin and hydroxypropyl methylcellulose, the stable integration and spatiotemporal controlled release of multiple ingredients in the hydrogel are achieved.
It achieves stable integration and sustained release of multiple drug components after intrauterine surgery, provides a drug delivery platform with a clear structure, stable system, and controllable release cycle, effectively preventing postoperative adhesions, promoting tissue repair and reducing inflammatory responses.
Smart Images

Figure CN120661523A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel, a preparation method and applications thereof. Background Art
[0002] Intrauterine surgery has important clinical significance in the treatment of uterine diseases (such as endometrial polyps, submucosal myomas, intrauterine adhesions, etc.). However, postoperative damage to the endometrium often leads to abnormal endometrial repair process, which in turn causes intrauterine re-adhesion. This re-adhesion may lead to serious consequences such as menstrual abnormalities, infertility and pregnancy-related complications. Especially in female patients who need to retain their reproductive function, effective prevention and control are needed. The current clinical methods used to prevent postoperative intrauterine re-adhesion mainly include mechanical isolation (such as placement of intrauterine balloons and intrauterine devices), drug treatment (such as hormone therapy, anti-inflammatory drugs) and biomaterial implantation (such as hyaluronic acid gel, etc.), but they all have certain limitations, such as short maintenance time, poor biocompatibility or inability to exert multiple pharmacological effects at the same time.
[0003] Tanshinone is a fat-soluble active ingredient extracted from Salvia miltiorrhiza. It has anti-inflammatory, anti-fibrosis and microcirculation-promoting effects, and shows certain potential in tissue repair and scar inhibition. Chuanxiongzine is an active ingredient extracted from Chuanxiong. It has anti-platelet aggregation, antioxidant and local blood flow improvement functions. Ferulic acid can effectively inhibit inflammatory responses and free radical damage, regulate collagen metabolism, and thus intervene in the fibrosis process.
[0004] Therefore, how to effectively embed components with multiple pharmacological activities into carriers and construct composite hydrogel carriers with both biological barrier and drug sustained-release functions has become the focus of current research on postoperative adhesion prevention after uterine surgery. Summary of the Invention
[0005] In response to the above problems, the present invention aims to provide a composition of tanshinone, ligustrazine and ferulic acid embedded in a hyaluronic acid hydrogel, which comprises the following components by mass percentage: tanshinone: 0.05% to 0.2%; ligustrazine: 0.1% to 0.6%; ferulic acid: 0.05% to 0.4%; high molecular weight sodium hyaluronate: 0.5% to 3.0%, wherein the molecular weight of the sodium hyaluronate is 800 to 1500 kDa; gelatin: 0.2% to 2.0%; hydroxypropyl methylcellulose. : 0.3% to 1.5%; glycerol or propylene glycol: 0.5% to 3.0%; microsphere encapsulation material: 1.0% to 5.0%, wherein the microsphere encapsulation material is selected from polylactic acid-glycolic acid copolymer PLGA or sodium alginate and chitosan complex; the rest is deionized water, which makes up 100%; wherein tanshinone, ligustrazine and ferulic acid are encapsulated in the microsphere encapsulation material in a core-shell structure, and the microspheres are further dispersed in a hyaluronic acid-gelatin-hydroxypropyl methylcellulose matrix to form a three-dimensional network structure.
[0006] As a preferred technical solution, the drug loading ratio of the core layer of the microspheres is 10% to 20% of the total microsphere mass. The three drugs are mixed and emulsified in a single emulsion system. The microsphere shell is 1.5% PLGA or is uniformly compounded by 2% sodium alginate and 1% chitosan in a pH 6.5 buffer solution, finally forming spherical particles with a particle size of 50 to 200 microns.
[0007] As a preferred technical solution, the gelatin is completely dissolved at a water bath temperature of 50°C to form a 2% (mass / volume) solution, which is then cooled to room temperature and added to the hydrogel system. The hydroxypropyl methylcellulose is added to the sodium hyaluronate solution by dry-dosing, and stirred at 25-30°C for 60-120 minutes to form a homogeneous liquid. The glycerol or propylene glycol is added at the end and stirred for 20 minutes to form a viscous transparent liquid.
[0008] As a preferred technical solution, the composite hydrogel finally obtained has a water content between 85% and 95%, a pH value range of 5.8 to 6.3, and a viscosity of 1000 to 3000 mPa·s at 25°C (measured under a shear rate of 1.0s -1 ), the hydrogel is in a translucent state and can form a coating layer with a thickness of 2 mm to 5 mm on the glass surface.
[0009] The present invention also provides a method for preparing the composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel, comprising the following steps:
[0010] S1. Forming a drug composite emulsion: dissolving tanshinone in ethanol to form an oil phase at a concentration of 1 mg / mL, and dissolving ligustrazine and ferulic acid in 0.1 M phosphate buffer at pH 7.0 to form an aqueous phase; forming a composite drug emulsion using a double emulsion method at a volume ratio of water:oil:water = 5:2:10, and emulsifying using a high-speed homogenizer at 10,000 rpm for 5 minutes;
[0011] S2. Construction of core-shell microspheres: The above emulsion was slowly added dropwise to a 1.5% PLGA solution or a 2% sodium alginate + 1% chitosan composite solution, and stirred continuously for 60 minutes. Core-shell microspheres were prepared by solvent evaporation or CaCl2 titration cross-linking method. The particle size was controlled to be 50-200 μm, and the powder was obtained by freeze drying.
[0012] S3. Prepare a three-component gel matrix: dissolve sodium hyaluronate in 4°C deionized water and stir magnetically for 12 hours to obtain a 1.5% solution; dissolve gelatin in a 50°C constant temperature water bath to obtain a 2% solution; add hydroxypropyl methylcellulose to the hyaluronic acid solution, stir at 25°C for 2 hours, then add glycerin and continue stirring for 30 minutes to obtain a gel precursor;
[0013] S4. Dispersion and gelation: The microspheres obtained in step S2 were slowly added to the gel precursor at a mass ratio of 1:20, while stirring until uniformly distributed. The resulting mixture was placed at 4° C. and allowed to stand for 24 hours to form a composite hydrogel with a three-dimensional network structure.
[0014] As a preferred technical solution, the calcium ion concentration of the CaCl2 cross-linking system is 0.3%, the cross-linking time is controlled to be 20 to 40 minutes, the ambient temperature is controlled to be 20 to 25°C, and after the cross-linking is completed, the microspheres are vacuum freeze-dried for 24 hours.
[0015] As a preferred technical solution, during the preparation of the sodium hyaluronate solution, a magnetic stirring rate of 300 rpm is adopted for 12 hours to obtain a viscous liquid which is stored at 4°C for future use.
[0016] As an optimal technical solution, the prepared composite hydrogel is stored at 4°C, the pH value is maintained between 5.8 and 6.3, the structure is stable for not less than 7 days in a sealed state, and the viscosity fluctuation range at room temperature within 7 days is less than ±10% of the initial value.
[0017] The present invention also provides the use of the composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel in the preparation of a medicine for preventing postoperative adhesions in the uterine cavity.
[0018] Beneficial effects
[0019] The invention provides a composite composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel. By introducing drug microspheres with a core-shell structure and constructing a three-dimensional gel network with sodium hyaluronate, gelatin and hydroxypropyl methylcellulose, the stable integration and spatiotemporal controlled release of multiple components in the hydrogel are achieved. The microsphere encapsulation materials used include PLGA and sodium alginate-chitosan complex, which can form a stable particle size structure through physical adsorption and ionic crosslinking, avoiding the migration and precipitation of drugs in the gel matrix. The composite hydrogel has good gelation and rheological properties, can form a continuous coverage on the wound surface, and achieve slow release through the drug particles encapsulated in the core layer, which helps to maintain the local drug concentration after surgery, thereby providing continuous intervention in the process of preventing postoperative adhesions. This composition provides an ideal drug delivery platform for postoperative intervention in the uterine cavity with a clear structure, stable system and controllable release cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of comparative experimental results (AFS score) of the present invention;
[0021] Figure 2 Schematic diagram of comparative experimental results (inflammatory factor expression levels) of the present invention;
[0022] Figure 3 Schematic diagram of comparative experimental results (tanshinone tissue residual concentration) of the present invention;
[0023] Figure 4 Schematic diagram of comparative experimental results (ligustrazine tissue residual concentration) of the present invention. DETAILED DESCRIPTION
[0024] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the examples. The examples are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0025] Example 1 (T1):
[0026] This embodiment provides a composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel, wherein the components, calculated by mass percentage, are as follows: tanshinone: 0.05%; ligustrazine: 0.1%; ferulic acid: 0.05%; high molecular weight sodium hyaluronate: 0.5%, wherein the molecular weight of the sodium hyaluronate is 800 kDa; gelatin: 0.2%; hydroxypropyl methylcellulose: 0.3%; propylene glycol: 0.5%; microsphere encapsulation material: 1.0%, wherein polylactic acid-glycolic acid copolymer (PLGA) is selected; and deionized water is supplemented to 100%.
[0027] The three drug components are encapsulated in a core-shell structure, with the drug loading in the core layer of the microspheres accounting for 10% of the total mass of the microspheres. The preparation method is as follows:
[0028] S1. Preparation of compound drug emulsion:
[0029] Tanshinone was dissolved in ethanol to prepare a 1 mg / mL oil phase solution. Ligustrazine and ferulic acid were separately dissolved in 0.1 M phosphate buffer, pH 7.0, to form an aqueous phase solution. The mixture was sequentially mixed in a water:oil:water ratio of 5:2:10 by volume and emulsified using a high-speed homogenizer at 10,000 rpm for 5 minutes to obtain a double emulsion system.
[0030] S2. Construction of core-shell microspheres:
[0031] The emulsion was slowly added dropwise to a 1.5% PLGA solution, magnetically stirred for 60 minutes to achieve preliminary encapsulation, and a solvent evaporation method was used to form core-shell structured microspheres with a particle size of 50 to 200 μm. The microspheres were then freeze-dried for 24 hours to obtain dry powdered microspheres.
[0032] S3. Preparation of three-component gel matrix:
[0033] Sodium hyaluronate was added to 4°C deionized water and magnetically stirred at 300 rpm for 12 hours to prepare a uniform solution with a concentration of 1.5%. Gelatin was added to a 50°C water bath and dissolved into a 2% solution. Hydroxypropyl methylcellulose was dry-added to the sodium hyaluronate solution and stirred at 25°C for 2 hours. Propylene glycol was then added and stirring continued for 30 minutes to obtain a transparent, viscous gel precursor.
[0034] S4. Microsphere dispersion and gelation treatment:
[0035] The dried microspheres obtained in step S2 were slowly added to the above-mentioned gel precursor at a mass ratio of microspheres to gel of 1:20, and stirred while adding to fully disperse them. After stirring, the mixed system was placed at 4°C for 24 hours to form a composite hydrogel with a three-dimensional network structure.
[0036] Example 2 (T2):
[0037] This embodiment provides a composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel. The components, calculated by mass percentage, are as follows: tanshinone: 0.2%; ligustrazine: 0.6%; ferulic acid: 0.4%; high molecular weight sodium hyaluronate: 3.0%, wherein the molecular weight of the sodium hyaluronate is 1500 kDa; gelatin: 2.0%; hydroxypropyl methylcellulose: 1.5%; glycerol: 3.0%; microsphere encapsulation material: 5.0%, wherein a composite material of sodium alginate and chitosan is selected, wherein the mass fraction of sodium alginate is 2% and the mass fraction of chitosan is 1%, and the two are premixed in a pH = 6.5 buffer solution; and deionized water is made up to 100%.
[0038] The tanshinone, ligustrazine and ferulic acid are encapsulated in the microsphere encapsulation material in a core-shell structure, and the microspheres are further uniformly dispersed in a gel matrix composed of hyaluronic acid-gelatin-hydroxypropyl methylcellulose to form a stable three-dimensional network structure.
[0039] S1. Preparation of compound drug emulsion:
[0040] Tanshinone was dissolved in ethanol to prepare a 1 mg / mL oil phase solution; ligustrazine and ferulic acid were separately dissolved in 0.1 M phosphate buffer, pH = 7.0, to form an aqueous phase solution; double emulsification was performed at a water:oil:water volume ratio of 5:2:10, and stirring was performed using a high-speed homogenizer at 10,000 rpm for 5 minutes to obtain a stable composite drug emulsion.
[0041] S2. Construction of core-shell microspheres:
[0042] The emulsion was slowly added dropwise to a 2% sodium alginate / 1% chitosan solution and magnetically stirred at 25°C for 60 minutes. Crosslinking was then performed by titration with a 0.3% CaCl₂ solution for 40 minutes. The resulting microspheres had a particle size of 50 to 200 μm and were freeze-dried in a vacuum for 24 hours to obtain a dry microsphere powder.
[0043] S3. Preparation of three-component gel matrix:
[0044] 3.0 g of high molecular weight sodium hyaluronate was added to 97 mL of 4°C deionized water and magnetically stirred at 300 rpm for 12 hours to prepare a 1.5% sodium hyaluronate solution. 2.0 g of gelatin was added to a 50°C water bath and completely dissolved to form a 2% solution. 1.5 g of hydroxypropyl methylcellulose was dry added to the hyaluronic acid solution and stirred at 25-30°C for 120 minutes to form a high-viscosity mixture. 3.0 g of glycerol was added and stirring was continued for 30 minutes to obtain a homogeneous gel precursor.
[0045] S4. Microsphere dispersion and gelation:
[0046] The dried microspheres obtained in step S2 were slowly added to the gel precursor at a mass ratio of 1:20. The mixture was uniformly mixed using magnetic stirring for 60 minutes, maintaining the stirring temperature at 20-25°C during the dispersion process. The final mixture was allowed to stand at 4°C for 24 hours to form a translucent, structurally stable, three-dimensional composite hydrogel.
[0047] Example three (T3):
[0048] This embodiment provides a composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel, wherein the components, calculated by mass percentage, are as follows: tanshinone: 0.12%; ligustrazine: 0.35%; ferulic acid: 0.20%; high molecular weight sodium hyaluronate: 2.0%, wherein the molecular weight of the sodium hyaluronate is 1000 kDa; gelatin: 1.0%; hydroxypropyl methylcellulose: 0.8%; glycerol: 1.5%; microsphere encapsulation material: 3.0%, wherein polylactic acid-glycolic acid copolymer (PLGA) is selected; and deionized water is supplemented to 100%.
[0049] Among them, tanshinone, ligustrazine and ferulic acid are co-encapsulated in the microsphere encapsulation material in the form of a core-shell structure. The obtained microsphere particle size is controlled between 50 and 200 μm and is dispersed in a three-dimensional gel matrix composed of sodium hyaluronate, gelatin and hydroxypropyl methylcellulose.
[0050] S1. Preparation of drug emulsion:
[0051] Tanshinone was dissolved in ethanol to prepare an oil phase with a concentration of 1 mg / mL, and ligustrazine and ferulic acid were respectively dissolved in 0.1 M phosphate buffer with a pH of 7.0 to form an aqueous phase. The mixture was mixed at a water:oil:water volume ratio of 5:2:10 and stirred for 5 minutes using a high-speed homogenizer at 10,000 rpm to prepare a stable composite drug double emulsion.
[0052] S2. Construction of core-shell microspheres:
[0053] The drug double emulsion was slowly added dropwise to a 1.5% PLGA solution and magnetically stirred for 60 minutes to form a preliminary encapsulation structure; the shell layer was polymerized by solvent evaporation to obtain core-shell structured microspheres with an average particle size of 50 to 200 μm; the obtained microspheres were freeze-dried for 24 hours to obtain a powdered dry microsphere material.
[0054] S3. Preparation of gel matrix:
[0055] 2.0 g of sodium hyaluronate was added to 4°C deionized water and magnetically stirred at 300 rpm for 12 hours to prepare a 1.5% solution. 1.0 g of gelatin was dissolved in a 50°C water bath to form a 2% (w / v) solution, which was cooled and set aside. 0.8 g of hydroxypropyl methylcellulose was dry-dosed into the sodium hyaluronate solution and stirred at 25-30°C for 90 minutes to form a homogeneous solution. 1.5 g of glycerol was then added and stirring continued for 20 minutes to obtain a transparent, viscous gel precursor.
[0056] S4. Microsphere dispersion and gelation:
[0057] The microspheres obtained in step S2 were slowly added to the above-mentioned gel precursor at a mass ratio of 1:20, and magnetically stirred at room temperature for 60 minutes to mix thoroughly. The mixture was placed in a 4°C environment for 24 hours to form a structurally uniform and stable three-dimensional composite hydrogel.
[0058] Comparative Example 1 (C1):
[0059] To verify the rationality of the content range of ligustrazine in the composition of the present application, comparative example 1 (C1) was set. The composition comprises the following components by mass percentage: tanshinone: 0.47%; ligustrazine: 0%; ferulic acid: 0.20%; high molecular weight sodium hyaluronate: 2.0%, molecular weight 1000kDa; gelatin: 1.0%; hydroxypropyl methylcellulose: 0.8%; glycerol: 1.5%; microsphere encapsulation material: 3.0%, selected from polylactic acid-glycolic acid copolymer (PLGA); and deionized water: supplemented to 100%.
[0060] Preparation method:
[0061] The steps are consistent with Example 3 (T3), including the formation of drug double emulsion, microsphere construction, gel matrix preparation and microsphere dispersion into gel.
[0062] Comparative Example 2 (C2):
[0063] In order to verify the effect of the mass percentage range of tanshinone defined in this application on the synergistic relationship of drug ratios and local tissue safety, comparative example 2 (C2) was set up, in which the tanshinone content was reduced to 0.02%.
[0064] The composition comprises the following components by mass percentage: tanshinone: 0.3%; ligustrazine: 0.45%; ferulic acid: 0.20%; high molecular weight sodium hyaluronate: 2.0%, molecular weight 1000kDa; gelatin: 1.0%; hydroxypropyl methylcellulose: 0.8%; glycerol: 1.5%; microsphere encapsulation material: 3.0%, selected from PLGA; and deionized water: supplemented to 100%.
[0065] Preparation method:
[0066] The same as Example 3 (T3), including the steps of forming a composite emulsion, encapsulating microspheres, constructing a gel matrix and dispersing microspheres into a gel.
[0067] Comparative Example 3 (C3):
[0068] In order to further verify the importance of the mass percentage range of high molecular weight sodium hyaluronate defined in this application to the formation of composite hydrogels and drug sustained release behavior, comparative example 2 (C2) was set up, and the sodium hyaluronate content was set to 0.3%, which is lower than the lower limit of 0.5% specified in this application.
[0069] The composition comprises the following components by mass percentage: tanshinone: 0.12%; ligustrazine: 0.35%; ferulic acid: 0.20%; high molecular weight sodium hyaluronate: 0.3%; molecular weight of 1000kDa; gelatin: 1.0%; hydroxypropyl methylcellulose: 0.8%; glycerol: 1.5%; microsphere encapsulation material: 3.0%, which is PLGA; and deionized water: supplemented to 100%.
[0070] Preparation process: refer to Example 3 (T3), including drug emulsion formation, microsphere encapsulation, three-component gel matrix construction and microsphere dispersion.
[0071] Comparative Example 4 (C4):
[0072] In order to verify the comprehensive advantages of the "tanshinone-ligustrazine-ferulic acid triple controlled-release microsphere system" described in this application in terms of synergistic anti-adhesion and sustained efficacy, comparative example four (C4) was set up.
[0073] The composition comprises the following components by mass percentage: 0.2% of tanshinone; 2.0% of high molecular weight sodium hyaluronate, with a molecular weight of about 1000 kDa; 1.0% of propylene glycol; and deionized water supplemented to 100%.
[0074] Among them, tanshinone was not encapsulated in microspheres, but was directly added to the hyaluronic acid solution in the form of ethanol solution to form a uniformly dispersed system without containing other drug ingredients and controlled-release structures.
[0075] Preparation method:
[0076] Dissolve 0.2 g of tanshinone in 2 mL of ethanol to prepare a 10 mg / mL solution; add 2 g of sodium hyaluronate to 97 mL of deionized water and stir magnetically at 4°C for 12 hours to form a uniform gel matrix; then slowly add the tanshinone ethanol solution and 1 g of propylene glycol to the hyaluronic acid solution, continue stirring for 30 minutes, and let stand at room temperature for 24 hours to form a tanshinone-HA gel.
[0077] Comparative experiment:
[0078] This experiment aimed to systematically evaluate the biological performance of the three different dosages and structural ratios of the triple microsphere composite hydrogels described in the examples of the present invention (T1, T2, and T3) in a postoperative intrauterine adhesion model, and compared them with four comparative samples (C1-C4) and two baseline control groups. By establishing a multi-dimensional indicator system, the comprehensive performance advantages of the present application formula in the anti-adhesion scenario were comprehensively demonstrated from the aspects of adhesion inhibition effect, tissue repair quality, inflammatory response degree, and drug release behavior.
[0079] This experiment particularly focuses on verifying whether the integrated drug release system constructed by "three-drug synergy + microsphere controlled release + three-dimensional gel scaffold" can continue to exert its efficacy and reduce the probability of adhesion formation throughout the postoperative repair cycle, and compare and analyze the performance degradation or limitations caused by the lack of any of these structural elements.
[0080] Female SD rats weighing 220 ± 20 g, healthy, virgin, and purchased from a reputable animal laboratory were used as experimental animals. After 7 days of adaptive feeding, all animals were randomly divided into groups of 15 rats per group.
[0081] A bilateral uterine injury model was established to simulate the tissue trauma environment after uterine surgery. The groups were shown in Table 1:
[0082] Table 1 Comparative experimental groups
[0083]
[0084] Steps for establishing an animal model of intrauterine adhesions:
[0085] Experimental animals: Female SD rats, weighing 220±20 g, sexually mature, from an SPF-grade experimental animal center;
[0086] Adaptive feeding: 7 days, room temperature 20-24°C, relative humidity 50-70%, 12-h light / dark cycle, free access to food and water;
[0087] Fasting and no drinking: Do not eat or drink for 12 hours before surgery and do not drink for 4 hours before surgery.
[0088] Anesthesia: intraperitoneal injection of 3% sodium pentobarbital, dose 30-40 mg / kg;
[0089] Animal fixation: fixed in supine position on the surgical pad with limbs fixed;
[0090] Treatment of the surgical area: shave the abdominal hair, disinfect with 75% ethanol three times, and cover with a sterile drape;
[0091] Aseptic operation: The entire process is carried out in a clean bench or aseptic operating environment.
[0092] Surgical steps: Uterine cavity injury induction model;
[0093] Incisional approach: Make a midline incision of about 2.0 cm in the lower abdomen, bluntly separate the abdominal wall tissue layer by layer, and expose the bilateral uterine horns;
[0094] Expose the uterus: Use sterile forceps to gently pull the uterine horns onto the in vitro operating platform, keeping it moist to prevent drying;
[0095] Electrocoagulation injury method: Use bipolar electrocoagulation forceps to ignite 35 points on the inner side of the endometrium with an output power of 1015W and an action time of 1 second per point; the electrocoagulation area is controlled to no more than 1 / 3 of the length of the uterus to avoid deep burning and perforation.
[0096] Control treatment (blank group): The uterus was exposed but no injury was applied, and only an equal volume of normal saline was injected.
[0097] Gel administration: The samples to be evaluated (T1-T3, C1-C4) were slowly injected into the uterine cavity according to the groups, with 0.25 mL injected into each horn, for a total of 0.5 mL;
[0098] Tissue reduction: Gently return the uterus to its original position in the abdominal cavity, avoiding twisting or folding;
[0099] Close the incision: Suture the peritoneum and skin in layers with absorbable sutures, and use suture clips to fix the epidermis if necessary;
[0100] Postoperative recovery: Place the animal on a warming blanket for monitoring and recovery. If there is no bleeding or abnormal behavior within 2 hours, the animal can be returned to the cage for breeding.
[0101] Antibiotic treatment: penicillin (40,000 IU) was injected subcutaneously daily for 3 consecutive days after surgery;
[0102] Wound care: observe for infection and suture removal, and replace the padding if necessary;
[0103] Success criteria: tissue sections showed endometrial shedding, inflammatory cell infiltration, glandular destruction, and a tendency toward adhesion formation; failure treatment: patients with no endometrial damage, surgical errors, or significant infection foci were excluded.
[0104] The experimental period is 14 days, covering the main stages of postoperative acute inflammation, proliferation and repair maturation. The specific sampling time points are as follows:
[0105] Day 3: Detect early inflammatory response and initial drug release;
[0106] Day 7: Observe the mid-stage tissue repair;
[0107] Day 14: Evaluate the long-term anti-adhesion effect and tissue structure recovery quality.
[0108] At each time point, 5 animals were taken from each group for autopsy, tissue sampling and index detection.
[0109] Four key evaluation indicators for the prevention and treatment of postoperative intrauterine adhesions were established, covering histological scoring, inflammatory factor analysis, fibrosis signal detection, and drug residue levels, forming a complete efficacy and mechanism evaluation system:
[0110] 1. Evaluation of intrauterine adhesion degree: AFS total score:
[0111] Evaluation system: The American Fertility Society (AFS) scoring system is used to score based on the following three indicators:
[0112] Adhesion extent (0–4 points): graded according to the proportion of the affected area of the uterine cavity;
[0113] Adhesion density (0–4 points): score according to the looseness / density of adhesion tissue;
[0114] Vascularization degree (0–4 points): The level of angiogenesis in the adhesion area was observed.
[0115] Scoring method: The total score ranges from 0 to 12 points, with higher scores indicating more severe adhesions. Three assessors perform blind scoring, and the average value is the final result.
[0116] 2. Inflammation level evaluation index: IL-6 concentration detection;
[0117] Indicator background: IL-6 is a representative cytokine of acute postoperative inflammatory response, and its level can reflect the inhibitory effect of drugs on local inflammatory response.
[0118] Detection method: Sample source: Uterine tissue was collected on the third day after surgery and homogenized; Analysis tool: ELISA kit (rat IL-6 specific) was used; Quantitative index: The unit is pg / mL, and the average of three replicate wells was taken.
[0119] 3. Fibrosis trend evaluation index: TGF-β1 concentration detection;
[0120] Indicator background: TGF-β1 is a key signaling factor in the occurrence of fibrosis. Its increase often indicates collagen deposition and fibrous adhesion formation in tissues.
[0121] Detection method: Sample source: uterine tissue homogenate on the 7th day after surgery; Detection technique: ELISA method (rat TGF-β1 paired antibody); Result unit: pg / mL, measured 3 times, and the average value was taken.
[0122] 4. Residual concentration of drugs in tissues: Tanshinone quantification.
[0123] Objective: To analyze the drug retention ability of the preparation in the uterus and evaluate its controlled release characteristics.
[0124] Detection time point: 3rd and 7th day after surgery (reflecting initial release and mid-term release)
[0125] Sample preparation: Approximately 100 mg of intact uterine tissue from the uterine horn was collected; tanshinone was extracted using a methanol-water extraction system; the supernatant was collected by centrifugation and filtered for quantitative analysis.
[0126] The experimental results are shown in Table 2 to Table 5:
[0127] Table 2 Comparative experimental results (AFS score)
[0128]
[0129] Table 3 Comparative experimental results (inflammatory factor expression levels, pg / mg)
[0130]
[0131]
[0132] Table 4 Comparative experimental results (tanshinone tissue residual concentration, μg / g)
[0133]
[0134] Table 5 Comparative experimental results (ligustrazine tissue residual concentration, μg / g)
[0135]
[0136] Data Analysis:
[0137] 1. Assessment of the severity of postoperative adhesions (Table 2, Figure 1 ): The AFS score is used to reflect the severity of postoperative pelvic or abdominal adhesions. A higher score indicates more severe adhesions.
[0138] The normal group always scored 0, indicating no adhesion, which is an ideal control baseline; the blank group maintained high scores of 9.5, 8.8 and 8.0 on days 3, 7 and 14, respectively, indicating severe inflammatory adhesions without intervention; T1-T3 are examples, and the scores gradually decreased over time, among which the T3 group performed best, with a score of only 1.2±0.3 on day 14, and adhesions were almost eliminated; among the comparative examples, the C1-C4 scores were significantly higher than those of T1-T3 as a whole, especially the C3 group (low hyaluronic acid group), which still had an adhesion score of 5.1±0.5 on day 14, indicating the importance of hyaluronic acid as a gel-forming and sustained-release matrix; the scores of the C2 group (low tanshinone) and the C4 group (unencapsulated) decreased slowly, indicating insufficient ability to maintain drug efficacy; Overall, the composite hydrogel system of the T3 group was significantly superior to the control groups in inhibiting adhesion formation and promoting tissue repair.
[0139] 2. Detection and analysis of inflammation levels (Table 3, Figure 2 ): In this experiment, the IL-6 level on the third day after surgery and the TGF-β1 level on the seventh day after surgery were selected as representative indicators of inflammatory response.
[0140] The normal group had 65.7±8.3 (IL-6) and 52.1±5.0 (TGF-β1), indicating a physiological state. The blank group had the highest expression levels, at 210.8 and 139.5, respectively, indicating that postoperative inflammation was not controlled. The T3 group had significantly lower levels than the control groups, with IL-6 dropping to 118.4±9.6 and TGF-β1 at 78.6±5.9, approaching physiological values. The C1 and C3 groups still had elevated levels of inflammatory factors, reflecting insufficient anti-inflammatory effects due to the type of medication or hyaluronic acid deficiency. The C2 group had higher IL-6 and TGF-β1 levels than the T3 group, suggesting that insufficient tanshinone content could not provide effective anti-inflammatory protection. In summary, the T3 group had the most significant anti-inflammatory effect at the critical postoperative time point.
[0141] 3. Analysis of changes in drug tissue residual concentration (Table 4, Figure 3 Table 5 Figure 4 ):The local tissue concentrations of tanshinone and ligustrazine on days 3, 7, and 14 after surgery were detected by LC-MS to reflect the controlled release performance of the hydrogel.
[0142] On day 14, the concentrations of tanshinone and ligustrazine in group T3 were 3.12 μg / g and 3.30 μg / g, respectively, maintaining high efficacy levels. Group C1, without ligustrazine, contained only tanshinone; on day 14, the concentration dropped to 1.42 μg / g, lower than that in group T3. Group C2 had a low initial tanshinone concentration, with concentrations nearing clearance levels by day 7 and becoming ineffective by day 14. Group C3 had a low hyaluronic acid content, resulting in rapid drug release and insufficient concentration maintenance. Group C4, without microspheres, had tanshinone concentrations below the critical threshold (approximately 0.99 μg / g) by day 7 and remained undetectable by day 14. Ligustrazine maintained a good sustained release in group T3, with residual efficacy remaining on day 14. Groups C2 and C3 also had residual efficacy, but this decreased more rapidly. Conclusion: The synergistic controlled release design of drug microsphere encapsulation and polymer matrix is key to achieving long-term anti-inflammatory and tissue repair in group T3.
[0143] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the foregoing embodiments. The foregoing embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.
Claims
1. A composition of tanshinone and ligustrazine combined with ferulic acid embedded in a hyaluronic acid hydrogel, characterized in that: The following components are included by mass percentage: Tanshinone: 0.05%-0.2%; Ligustrazine: 0.1% to 0.6%; Ferulic acid: 0.05% to 0.4%; High molecular weight sodium hyaluronate: 0.5% to 3.0%, wherein the molecular weight of the sodium hyaluronate is 800 to 1500 kDa; Gelatin: 0.2%-2.0%; Hydroxypropyl methylcellulose: 0.3% to 1.5%; Glycerin or propylene glycol: 0.5% to 3.0%; Microsphere encapsulation material: 1.0% to 5.0%, wherein the microsphere encapsulation material is selected from polylactic acid-glycolic acid copolymer PLGA or a complex of sodium alginate and chitosan; The rest is deionized water, making up to 100%; Tanshinone, ligustrazine and ferulic acid are encapsulated in the microsphere encapsulation material in a core-shell structure, and the microspheres are further dispersed in a hyaluronic acid-gelatin-hydroxypropyl methylcellulose matrix to form a three-dimensional network structure.
2. The composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel according to claim 1, characterized in that: The core layer of the microspheres has a drug loading ratio of 10% to 20% of the total microsphere mass. The three drugs are mixed and emulsified in a single emulsion system. The microsphere shell is 1.5% PLGA or is uniformly compounded by 2% sodium alginate and 1% chitosan in a pH 6.5 buffer solution, ultimately forming spherical particles with a particle size of 50 to 200 microns.
3. The composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel according to claim 1, characterized in that: The gelatin is completely dissolved in a water bath at 50° C. to form a 2% mass-to-volume solution, which is then cooled to room temperature and added to the hydrogel system. The hydroxypropyl methylcellulose is dry-dosed into the sodium hyaluronate solution and stirred at 25-30° C. for 60-120 minutes to form a homogeneous liquid. The glycerol or propylene glycol is added at the end and stirred for 20 minutes to form a viscous transparent liquid.
4. The composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel according to claim 1, characterized in that: The pH value of the final composite hydrogel is in the range of 5.8-6.3, and the viscosity is in the range of 1000-3000 mPa·s at 25°C, wherein the measurement condition is a shear rate of 1.0s -1 , the hydrogel is in a translucent state.
5. A method for preparing the composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Forming a drug composite emulsion: dissolving tanshinone in ethanol to form an oil phase at a concentration of 1 mg / mL, and dissolving ligustrazine and ferulic acid in 0.1 M phosphate buffer at pH 7.0 to form an aqueous phase; forming a composite drug emulsion using a double emulsion method at a volume ratio of water:oil:water = 5:2:10, and emulsifying using a high-speed homogenizer at 10,000 rpm for 5 minutes; S2. Construction of core-shell microspheres: The above emulsion was slowly added dropwise to a 1.5% PLGA solution or a 2% sodium alginate + 1% chitosan composite solution, and stirred continuously for 60 minutes. Core-shell microspheres were prepared by solvent evaporation or CaCl2 titration cross-linking method. The particle size was controlled to be 50-200 μm, and the powder was obtained by freeze drying. S3. Prepare a three-component gel matrix: dissolve sodium hyaluronate in 4°C deionized water and stir magnetically for 12 hours to obtain a 1.5% solution; dissolve gelatin in a 50°C constant temperature water bath to obtain a 2% solution; add hydroxypropyl methylcellulose to the hyaluronic acid solution, stir at 25°C for 2 hours, then add glycerin and continue stirring for 30 minutes to obtain a gel precursor; S4. Dispersion and gelation: The microspheres obtained in step S2 were slowly added to the gel precursor at a mass ratio of 1:20, while stirring until uniformly distributed. The resulting mixture was placed at 4° C. and allowed to stand for 24 hours to form a composite hydrogel with a three-dimensional network structure.
6. The preparation method according to claim 5, characterized in that The calcium ion concentration of the CaCl2 cross-linking system is 0.3%, the cross-linking time is controlled to be 20 to 40 minutes, the ambient temperature is controlled to be 20 to 25°C, and after the cross-linking is completed, the microspheres are vacuum freeze-dried for 24 hours.
7. The preparation method according to claim 5, characterized in that During the preparation of the sodium hyaluronate solution, a magnetic stirring rate of 300 rpm was used for 12 hours to obtain a viscous liquid which was stored at 4° C. for later use.
8. The preparation method according to claim 5, characterized in that The prepared composite hydrogel is stored at 4° C., with a pH value maintained between 5.8 and 6.
3. The structure is stable for no less than 7 days in a sealed state, and the viscosity fluctuation range at room temperature within 7 days is less than ±10% of the initial value.
9. Use of the composition of tanshinone and ligustrazine combined with ferulic acid embedded in hyaluronic acid hydrogel according to any one of claims 1 to 4 in the preparation of a medicament for preventing postoperative adhesions in the uterine cavity.
Citation Information
Patent Citations
Pharmaceutical composition for treating and preventing adhesion after abdominal operation
CN103948617A
Hyaluronic acid-gelatin composite hydrogel carrying PLGA microspheres and preparation method thereof
CN111228565A
Nano hydrogel for preventing abdominal adhesion as well as preparation method and application of nano hydrogel
CN118649294A
Hyaluronic acid-based temperature-sensitive hydrogel SV-coated HP as well as preparation method and application of hyaluronic acid-based temperature-sensitive hydrogel SV-coated HP
CN119746037A
Slow-release gel preparation for endometrial repair and preparation method thereof
CN120267603A